Combined robotic-aided gait training and physical therapy improve functional abilities and hip kinematics during gait in children and adolescents with acquired brain injury. (23rd April 2015) - Beretta, Elena; Romei, Marianna; Molteni, Erika; Avantaggiato, Paolo; Strazzer, Sandra
Abstract: Purpose : To evaluate the combined effect of robotic-aided gait training (RAGT) and physical therapy (PT) on functional abilities and gait pattern in children and adolescents exiting acquired brain injury (ABI), through functional clinical scales and 3D-Gait Analysis (GA). Methods : A group of 23 patients with ABI underwent 20 sessions of RAGT in addition to traditional manual PT. All the patients were evaluated before and after the training by using the Gross Motor Function Measures (GMFM) and the Functional Assessment Questionnaire. Ambulant children were also evaluated through the 6 Minutes Walk Test (6MinWT) and GA. Finally, results were compared with those obtained from a control group of ABI children who underwent PT only. Results : After the training, the GMFM showed significant improvement in both dimensions 'D' (standing) and 'E' (walking). In ambulant patients the 6MinWT showed significant improvement after training and GA highlighted a significant increase in cadence, velocity and stride length. Moreover, hip kinematics on the sagittal plane revealed a statistically significant increase in range of motion (ROM) during the whole gait cycle, increased hip extension during terminal stance and increased ROM during the swing phase. Conclusions : The data suggest that the combined programme RAGT + PT induces improvements in functional activities and gait pattern in children and adolescents with ABI and demonstrated it to be an elective tool for the maintenance of the patients' full compliance throughout the rehabilitative programme.